2019
DOI: 10.1158/1538-7445.sabcs18-p1-18-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-18-01: Incidence of hypocalcemia in patients with metastatic breast cancer under treatment with denosumab: A non-inferiority phase III trial assessing prevention of symptomatic skeletal events (SSE) with denosumab administered every 4 weeks versus every 12 weeks: SAKK 96/12 (REDUSE)

Abstract: Background Monthly Denosumab (DN) has shown superiority over zoledronic acid (ZA) in delaying skeletal related events. Randomized trials have shown that ZA given every 12 weeks (q12w) is non-inferior to ZA given every 4 weeks (q4w). The primary endpoint of the REDUSE-trial is non-inferiority for SSE for DN q12w versus q4w. Here we present early data for hypocalcemia (HC), a secondary endpoint. Methods Patients with bone metastasis from breast cancer (BC) not pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, rate of hypocalcemia in this trial was much higher than observed in registration trials despite mandatory vitamin D and calcium supplementation (31.6% vs <15%). [36][37][38]…”
Section: Recent and Ongoing Randomized Trialsmentioning
confidence: 99%
“…Interestingly, rate of hypocalcemia in this trial was much higher than observed in registration trials despite mandatory vitamin D and calcium supplementation (31.6% vs <15%). [36][37][38]…”
Section: Recent and Ongoing Randomized Trialsmentioning
confidence: 99%
“…The estimated enrollment is 1,380 patients with BC or prostate cancer, and the estimated study competition date is December 2022. Preliminary data published in the form of abstracts and presented in the San Antonio Breast Cancer Symposium 2018 (40) show that denosumab-related hypocalcemia is less frequent with administration every 12 weeks.…”
Section: Bone Modifiersmentioning
confidence: 99%